Radiographic and scanning electron microscopic assessment of root canal filling remnants after endodontic re-instrumentation - Santos, Luciane Geanini Pena; Felippe, Wilson Tadeu; Souza, Beatriz Dulcineia Mendes; Konrath, Andrea Cristina; Cordeiro, Mabel Mariela Rodríguez; Felippe, Mara Cristina Santos (Brazilian Dental Science, 2017)
Objective: Failures in endodontic treatment may occur by several reasons. Endodontic retreatment is an interesting alternative to manage this clinical problem. However, it is not possible to completely remove the root canal filling by any current retreatment technique. The aim of this study was to evaluate the presence of residual root canal filling materials after endodontic re-instrumentation. Material and Methods: Sixty extracted anterior human teeth were prepared by step-back technique with Flexofiles, K-files and Gates-Glidden (GG) burs. Between the use of each file or bur, root canals were irrigated with sodium hypochlorite (NaOCl). Smear layer was removed by irrigation with ethylenediaminetetraacetic acid and NaOCl. After drying with paper points the root canals were randomly divided into 5 groups (n = 12), according to filling material: Resilon cones/Real Seal sealer or gutta-percha cones and Endofill, Sealapex, AH Plus or MTA Fillapex sealers. After one week, root canal fillings were removed using Eucaliptol and K-files. Root canals were re-instrumented with K-files and GG burs sized larger than the first ones. The removal of root canal filling material was analyzed by radiography and scanning electron microscopy (SEM). Statistical analysis was performed using Binary Logistic Regression test (P < 0.05). Results: Radiographic and SEM analysis showed that material from the MTA Fillapex group was better removed than that from Endofill, Sealapex, AH Plus and Real Seal groups. Conclusion: After re-instrumentation, MTA Fillapex group showed less remnants into the root canals than Endofill, Sealapex, AH Plus and Real Seal groups. Residual material was most often found in the apical third. Keywords Dental radiography; Endodontic retreatment; Root canal filling materials; Scanning electron microscopy.